Excellent performance MWCNTs-GONRs/Ni(OH)2 electrode for outstanding supercapacitors. Issue 15 (15th October 2019) - Qiu, Hengrui; An, Shengli; Sun, Xuejiao; Yang, Huimin; Zhang, Yongqiang; He, Wenxiu
Abstract: Due to the unconventional properties of MWCNTs-GONRs (multiwalled carbon nanotubes-graphene oxide nanoribbons), we have tried to use it as a carbon resource for supercapacitors. MWCNTs-GONRs/Ni(OH)2 electrode was obtained by hydrothermal method. Velvet α-Ni(OH)2 was prepared above NF (nickel-foam) loaded with MWCNTs-GONRs. This layered design can effectively promote the diffusion of ions and increase the active site for MWCNTs-GONRs/Ni(OH)2 electrode, thus enhancing the electrochemical performance. The electrode exhibits extraordinary electrochemical performances in electrochemical testing, such as supernal specific capacitance (1713.2 F g −1 ) and prominent working time. In addition, supercapacitors was assembled with MWCNTs-GONRs/Ni(OH)2 and active carbon as materials. Which represents a prominent energy density (41.23 Wh kg −1 ), high power (6.80 kW kg −1 ) and prominent cycling stability property (95.18%, 3000 times). The electrode prepared in this work provides a clue to enlighten people for energy storage.